Regulatory network analysis of Dclk1 gene expression reveals a tuft cell-ILC2 axis that inhibits pancreatic tumor progression - Giovanni Valenti; Pasquale Laise; Feijing Wu; Ryota Takahashi; Tuo Ruan; Alessandro Vasciaveo; Zhengyu Jiang; Hiroki Kobayashi; Masaki Sunagawa; Moritz Middelhoff; Henrik Nienhüser; Na Fu; et al. (Cell Reports)
Summary: Doublecortin-like kinase 1 (Dclk1) expression identifies cells that are rare in normal pancreas but occur with an increased frequency in pancreatic neoplasia. The identity of these cells has been a matter of debate. We employed Dclk1 reporter mouse models and single-cell RNA sequencing (scRNA-seq) to define Dclk1-expressing cells. In normal pancreas, Dclk1 identifies subsets of ductal, islet, and acinar cells. In pancreatic neoplasia, Dclk1 identifies several cell populations, among which acinar-to-ductal metaplasia (ADM)-like cells and tuft-like cells are predominant. These two populations play opposing roles, with Dclk1+ ADM-like cells sustaining and Dclk1+ tuft-like cells restraining tumor progression. The generation of Dclk1+ tuft-like cells requires the transcription factor SPIB and is sustained by a paracrine loop involving type 2 innate lymphoid cells (ILC2s) and cancer-associated fibroblasts (CAFs) that provide interleukin (IL)-13 and IL-33, respectively. Dclk1+ tuft-like cells release angiotensinogen to restrain tumor progression. Overall, our study defines pancreatic Dclk1+ cells and unveils a protective tuft cell-ILC2 axis against pancreatic neoplasia.